Puzzle: Hound of the Baskervilles. - Wysocki, Charles; Buffalo Games, LLC (Buffalo, NY Buffalo Games, LLC, 2014)
You'll feel like you've stepped into a quaint New England town as you put together this puzzle of a travelling storyteller recounting tales of romance and mystery to the local townspeople provided by the publisher
Age 14+.
Keywords: storytellers; New England; puzzles and games